2019
DOI: 10.1111/psyp.13477
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of cognitive‐motor expertise on brain dynamics of anticipatory‐based outcome processing

Abstract: The ability to anticipate the outcome of others' actions is necessary for effective interactions in dynamic and uncertain environments and is a hallmark of the superior performer in reactive sport situations such as those that occur in table tennis, defensive volleyball play, or the fielding of a baseball. In the case of skilled cognitive-motor performance, predictive theories of action observation suggest that one predicts an opponent's actions through the processing of kinematic cues and the generation of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…In this study as in our previous studies using the same video materials (Lu et al, 2020;Wang, Lu, et al, 2019;Zhao et al, 2018), novices as well as expert players predicted the trajectory of a ball with accuracy levels above chance for videos that were occluded at the moment of the serve and for videos showing the final ball trajectory. This accuracy higher than chance for novices may have reduced the contribution of task difficulty to group differences (Xu et al, 2016).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In this study as in our previous studies using the same video materials (Lu et al, 2020;Wang, Lu, et al, 2019;Zhao et al, 2018), novices as well as expert players predicted the trajectory of a ball with accuracy levels above chance for videos that were occluded at the moment of the serve and for videos showing the final ball trajectory. This accuracy higher than chance for novices may have reduced the contribution of task difficulty to group differences (Xu et al, 2016).…”
Section: Discussionmentioning
confidence: 60%
“…The ocular artifact–corrected EEG data were then segmented, starting 500 ms prior to the frame of racket‐ball contact onset to 1,000 ms after the onset for each experimental condition. The baseline was corrected using the −500 to 0 ms pre‐contact period (Lu et al., 2020). Epochs with signals that exceeded ±100 μV were rejected.…”
Section: Methodsmentioning
confidence: 99%
“…These findings suggest that the theta and alpha power of specific brain regions are related to the accuracy and professionalism of shooting. Lu et al found that a larger oscillatory activity in both the mid-frontal theta and parieto-occipital alpha in experts suggested an adaptive neural preparatory process with highly developed motor skills in complex tasks, characterized by high attentional demands, anticipation of uncertainty, and the integration of multiple visual cues [ 26 ]. This provides a theoretical support for us to study the neural activities in the process of shooting preparation for competitive tasks.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the theta-band oscillation over the midfrontal cortex reflects conflict detection and resolution processes ( Cohen and Donner, 2013 ) and is modulated by an individual’s expertise during action observation. Brain dynamics during action anticipation was examined by presenting participants with edited videos of table tennis serve movement in a previous study ( Lu et al. , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Lu’s study (2020) , the goal of the table tennis opponent’s serve action (i.e. serving the ball to a specific position) could be inferred from kinematic information.…”
Section: Introductionmentioning
confidence: 99%